Graphene Oxide Nanosheets Tailored With Aromatic Dipeptide Nanoassemblies for a Tuneable Interaction With Cell Membranes - Trapani, Giuseppe; Caruso, Viviana Carmela Linda; Cucci, Lorena Maria; Attanasio, Francesco; Tabbì, Giovanni; Forte, Giuseppe; La Mendola, Diego; Satriano, Cristina (Frontiers in Bioengineering and Biotechnology, 2020)
Engineered graphene-based derivatives are attractive and promising candidates for nanomedicine applications because of their versatility as 2D nanomaterials. However, the safe application of these materials needs to solve the still unanswered issue of graphene nanotoxicity. In this work, we investigated the self-assembly of dityrosine peptides driven by graphene oxide (GO) and/or copper ions in the comparison with the more hydrophobic diphenylalanine dipeptide. To scrutinise the peptide aggregation process, in the absence or presence of GO and/or Cu2+, we used atomic force microscopy, circular dichroism, UV-visible, fluorescence and electron paramagnetic resonance spectroscopies. The perturbative effect by the hybrid nanomaterials made of peptide-decorated GO nanosheets on model cell membranes of supported lipid bilayers was investigated. In particular, quartz crystal microbalance with dissipation monitoring and fluorescence recovery after photobleaching techniques were used to track the changes in the viscoelastic properties and fluidity of the cell membrane, respectively.